IDENTIFIKASI JENIS DAN PEMANFAATAN ROTAN DI NEGERI HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Andjela Sahupala; Troice Siahaya (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This research aims to understand the types and forms of use of rattan in Hatusua State, Kairatu District, West Seram Regency. This research was carried out by direct observation and identification in the field. What is observed is: flowers, leaves, fruit, stems and other organ characteristics. Furthermore, the approach process in this research involves identifying the external parts of the plant body in each type. According to the results obtained from research in Hatusua State, Kairatu District, West Seram Regency, it can be concluded as follows: The types of rattan found in Hatusua State are 4 types of rattan, namely Deer Reed Rattan (Daemonorops robustus warb) a small portion of the people use it for Chair and table frames, Wax Rattan or Javanese Rattan (Calamus javensis) can be used for ropes to tie bamboo to mayang trees for containers for holding mayang water, materials for making nyiru (trays), mulch clamping material on agricultural land, material for making tifa, woven material, Tuni Rattan (Calamus amphybolus becc) is used for making furniture. and Tohiti rattan (Calamus inops) is rarely used, because most local people prefer wax or Javanese rattan (Calamus javensis).